ANALISIS FAKTOR KONFIRMATORI KUALITAS PELAPORAN KEUANGAN - Fanani, Zaenal (Journal of Accounting and Strategic Finance, 2011)
The purpose of this study was to test whether the indicators of the quality of accounting-based financial reporting (accrual quality, persistence, prediktabilita, and income smoothing) and market-based (value relevance, timeliness, and conservatism) differ from one another and contribute to the formation of quality financial reporting. This study sample of manufacturing firms using data analysis techniques confirmatory factor analysis. The results of this study showed no overlap between the seven indicators of quality of financial reporting. This difference makes each indicator representing it self in the form of financial reporting quality variables. Quality financial reporting is supported by five indicators, namely the quality of financial reporting of accounting-based (accrual quality, prediktabilita, and income smoothing), quality of financial reporting of market-based (value relevance, and conservatism). Two other indicators of persistence and timeliness does not indicate suitability and appropriateness or unidimensionalitas in shaping the quality of financial reporting.   Keywords: Financial Reporting Quality, Accounting-Based, Market-Based